4 - The Politicization of the Education System: Implications for Peace in Sudan - Hala Asmina Guta, (Africa Media Review, 2009)
This article takes a closer look at the education system in Sudan and its role in social cohesion/division. It analyzes themes run in approved textbooks. The findings of this article can be summarized around three main points: the curriculum constructs an exclusionary version of Sudanese identity that is practically the same as Northern Arabic Muslim identity; heroism is associated with war and history lessons are centred on the history of wars; and, war and violence are always linked and consequently legitimized. The article argues that educational institutions in Sudan fail to create harmony and acceptance among different ethnic groups and perpetuate prejudice and violence. An urgent reform in the curriculum is needed.